The nonlinear impact of political institutional quality on financial inclusion - Lachebeb, Zakaria; Ismail, Normaz Wana; Niaz Ahmad, Mohd Naseem; Slesman, Ly (University of Malaya, 2021)
This study investigates the nonlinear relationship between political institutions and financial inclusion in a panel of 74 developing countries using annual data from 2007 to 2016. This study uses the financial inclusion index and two components of financial inclusion, namely access and availability to financial services. The estimated model using the generalized method of moments (GMM) system (SYS-GMM) revealed that democracy has a significant U-shaped impact on the financial inclusion index, and access to and availability of financial services. However, a similar effect on the index of financial inclusion is not robust to the removal of outliers. Overall, the findings confirm that a better quality of political institutions, i.e., when it exceeds an inflection/threshold point, would lead to a higher degree of financial inclusion—as captured by the access and availability of financial services, for example the number of deposit accounts, automated teller machines (ATM), and bank branches. Our finding of the U-shaped impact on overall financial inclusion indicators are robust to outliers. The implication is that countries with a better quality of political institutions are predicted to be associated with high levels of financial inclusion. Whereas, countries with a low quality of (democratic) political institutions hinder the delivery of financial inclusion.